Analysis Of Job Satisfaction, Leadership, Human Capital, Corporate Governance, Tax Awareness, And Firm Performance - Nurjannah Nurjannah; Siti Rumenta; Muhammad Arif Rahman (Pusat Riset dan Inovasi Nasional, 2023)
This research investigates the interplay between job satisfaction, leadership, human capital, corporate governance, tax awareness, and firm performance. The study aims to understand the intricate relationships among these factors in organizational success. Employing a qualitative research design, this study utilizes purposive sampling to gather data from participants representing various organizational levels. Data analysis involves thematic analysis to uncover patterns, themes, and relationships within the data. Results reveal nuanced insights into the influence of leadership styles, employee satisfaction, governance structures, and tax consciousness on firm performance. The findings underscore the significance of effective leadership, robust human capital management, sound corporate governance practices, and tax awareness in enhancing organizational outcomes. This study contributes to a deeper understanding of the multifaceted dynamics shaping organizational success in contemporary business environments.